2019
DOI: 10.1155/2019/2093612
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pregnancy Complicated with Evans Syndrome with Sequential Development of Autoimmune Warm Antibody Hemolytic Anemia and Idiopathic Thrombocytopenic Purpura

Abstract: The simultaneous or sequential development of autoimmune hemolytic anemia (AIHA) and idiopathic thrombocytopenic purpura (ITP) is known as Evans syndrome. We experienced a case of Evans syndrome that developed AIHA during pregnancy and ITP long after delivery. The patient was a 35-year-old pregnant woman (gravida 2, para 1). A routine blood test at 28 weeks of gestation revealed moderate macrocytic anemia. Her haptoglobin level was markedly low, and a direct antiglobulin test (DAT) was positive. Based on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…There was no thrombocytopenia reported in this neonate at any time. Following this systematic review, a search for more recent reports revealed five other case reports, three of which described healthy babies with no complications 15–17. The fourth reported the pregnancy ending with stillborn twins of 28 weeks gestation 18.…”
Section: Discussionmentioning
confidence: 99%
“…There was no thrombocytopenia reported in this neonate at any time. Following this systematic review, a search for more recent reports revealed five other case reports, three of which described healthy babies with no complications 15–17. The fourth reported the pregnancy ending with stillborn twins of 28 weeks gestation 18.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current protocols utilize varying doses of empiric parenteral iron supplementation in the setting of blood product refusal [ 6 , 7 ]. In one case report, a pregnant patient who developed severe ES was treated empirically with parenteral iron despite normal serum iron studies and demonstrated positive results and recovery of hematologic parameters [ 9 ]. While there are anecdotal case reports describing the use of parenteral iron in isolated AIHA and ES, current data are limited and need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature search of cases of ES in pregnancy, a 2010 review article identified a total of 14 pregnancies, with data available for 9 cases [2]. Case reports of an additional 5 cases have since been published [2][3][4][5]. Of these 14 pregnancies for which data is available, 5 were complicated by preeclampsia, 3 by postpartum hemorrhage, and 1 with placental abruption.…”
Section: Discussionmentioning
confidence: 99%
“…The trigger for the onset of ES in this patient was unclear. Cytokine activity in pregnancy may lead to increased autoimmunization against red blood cells [4], leading to higher rates of AIHA in pregnancy. About half of patients with ES have other immune disorders such as systemic lupus erythematosus, immunodeficiencies, or autoimmune lymphoproliferative disorders.…”
Section: Discussionmentioning
confidence: 99%